Investigating the Effect of Dexmedetomidine in Controlling Postoperative Emergence Agitation in Children under Sevoflurane Anesthesia - Mitra Golmohammadi; Shahryar Sane; Somayeh Ghavipanjeh Rezaei; Rana Hosseini; Enas R. Alwaily; Beneen M. Hussien; Ramin Mohammadpour; Nazila Rahmani; Behzad Kazemi Haki (Anesthesiology Research and Practice, 2024)
Introduction. Emergence agitation (EA) is one of the common problems during recovery from general anesthesia, especially in children. In this study, we investigated the effect of dexmedetomidine on the control of agitation after anesthesia with sevoflurane in children. Method. This randomized control-placebo, double-blind prospective clinical trial was conducted on seventy-six children between 2 and 7 years with ASA (American Society of Anesthesiologists) class I who were candidates for elective adenoidectomy surgery and tonsillectomy. Participants were selected by an available sampling method. Patients were randomly placed in one of the two groups D (dexmedetomidine 0.5 μg/kg infusion within ten minutes) or P (placebo: normal saline infusion within ten minutes). A four-point scale evaluated agitation. Pain evaluation was done by FLACC (faces, legs, activity, cry, and consolability). The statistical software was SPSS version 23. P<0.05 was considered statistically significant. Results. The level of agitation was significantly lower in the intervention group (P<0.05), except after 40 minutes in the PACU (Post Anesthesia Care Unit) (P=1.00). Patients in the control group experienced high pain scores when admitted at PACU, 10, 20, and 30 minutes after admission at PACU (P<0.05). Pethidine and metoclopramide prescriptions in the intervention group were lower than in the control group (P<0.05). Shivering occurred in five patients in the intervention group and nine in the control groups (P=0.032). Hypotension that required intervention occurred in 3 patients in the intervention group and one in the control group (P=0.024). Conclusion. Our trial demonstrated that the prescription of 0.5 μg/kg of dexmedetomidine within ten minutes after intubation significantly reduced the EA frequency, pain severity, analgesic consumption, and PONV (postoperative nausea and vomiting). However, it caused delays in the emergence from anesthesia. This trial is registered with IRCT20160430027677N14.